Characterization and antioxidant assay of yellow frangipani flower (Plumeria alba) extract - Ahmad Fathoni; Tarso Rudiana; Adawiah Adawiah (Jurnal Pendidikan Kimia (JPKim), 2019)
Yellow frangipani flowers (Plumeria alba) are plants that commonly found in the tropics, including Indonesia. Frangipani utilization has not optimum and research about it has not many conducted. This study aims to characterize and test the antioxidant activity of frangipani flower extract. The extraction conducted by maceration method using n-hexane, ethyl acetate, and methanol as solvents. Characterization includes phytochemicals assay (alkaloids, flavonoids, terpenoids, phenolic hydroquinone, tannin-polyphenols, and saponins), total phenolic assay, and total flavonoid assay. Antioxidant test using DPPH radical scavenging assay. The results of the characterization showed that frangipani flower extract positively contained alkaloid, flavonoids, tannins compounds in all solvent phases. Terpenoids are positive in n-hexane and ethyl acetate extract, while saponins are positive in methanol extract. The total phenolic content of n-hexane, ethyl acetate, and methanol extract were 3.6 mgGAE/g; 27.74 mgGAE/g; and 35.23 mgGAE/g. The total flavonoid content of n-hexane, ethyl acetate, and methanol extract were respectively 0.8 mgQE/g; 12.18 mgQE/g; 19.9 mgQE/g. The strongest antioxidant activity is possessed by ethyl extract, followed by methanol extract, and the last are n-hexane extract.Keywords:Antioxidant; frangipani flower; phytochemical; total phenolic; total flavonoid